Effect of low-temperature aging on the mechanical behavior of ground Y-TZP - Pereira, G. K. R.; Amaral, M. [UNESP]; Cesar, P. F.; Bottino, M. C.; Kleverlaan, C. J.; Valandro, L. F. (Elsevier B.V., 2015)
This study evaluated the effects of low-temperature aging on the surface topography, phase transformation, biaxial flexural strength, and structural reliability of a ground Y-TZP ceramic. Disc-shaped specimens were manufactured and divided according to two factors: "grinding" - without grinding (as-sintered, Ctrl), grinding with an extra-fine diamond bur (25 mu m Xfine) and coarse diamond bur (181 mu m Coarse); and "low-temperature-aging" (absence or presence). Grinding was performed using a contra-angle handpiece under water-cooling. Aging was performed in an autoclave at 134 degrees C, under 2 bar, over a period of 20 h. Surface topography analysis showed an increase in roughness based on grit-size (Coarse>Xfine>Ctrl), and aging promoted different effects on roughness (Ctrl Ag<Ctrl; Xfine Ag<Xfine; Coarse Ag>Coarse). Grinding and aging promoted an increase in the amount of m-phase, although different susceptibilities to degradation were observed. Weibull analysis showed an increase in characteristic strength after grinding (Coarse=Xfine>Ctrl); however, distinct effects were observed for aging (Ctrl<Ctrl Ag; Xfine=Xfine Ag; Coarse>Coarse Ag). Weibull moduli were statistically similar. Grinding promoted an increase in characteristic strength as a result of an increase in m-phase content; when the Y-TZP surface was ground by coarse diamond burs followed by aging, characteristic strength was reduced, meaning the low-temperature degradation appeared to intensify for rougher Y-TZP surfaces. Copyright (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Grinding; Hydrothermal aging; Low-temperature degradation; Zirconium oxide partially stabilized by yttrium; Phase transformation; Mechanical properties; Structural reliability